THE EFFECTIVENESS OF THE COMBINATION OF FOOT SPA THERAPY AND BUEGER'S ALLEN EXERCISE AGAINST THE VALUE OF ANKLE BRACHIAL INDEX IN ELDERLY WITH DIABETES MELLITUS - Diah Ratnawati; Sang Ayu Made Adyani; Ritanti Ritanti (Universitas Muhammadiyah Tangerang, 2020)
Elderly with Diabetes mellitus (DM) is experienced for decreasing the quality of peripheral blood flows that identified numbness, tingling, and decreased foot sensitivity. This condition is impacted by the occurrence of leg ulcer complications and to worsen for amputating for the lower extremities. This research purpose to exam the effectiveness of a combination of foot spa therapy and Bueger's Allen Exercises on the value of the ankle-brachial index in the elderly with diabetes mellitus. The method used in this research is quasi-experimental (pre-test and post-test comparison group design). The population in this study was elderly with DM type 2. The number of sample in this study were 114 samples, were divides into 3 groups, each group consisting of 38 respondents. The first group was foot spa therapy intervention, the second group was Bueger’s Allen Exercise intervention, and the third group was the combination group. The data was collected by measuring the ABI pre-test and post-test in each group. The interventions were carried out about 24 sessions for 8 weeks. The results of the study obtained in pairs of T-test results showed a meaningful difference before and after the therapy with the value P = 0,000 (P < 0.05). In addition, the LSD test received the data mean difference combination therapy compared with Bueger's Allen Exercises of 0.0571 (Sig. = 0,000) and compared to the Foot Spa of 0.0796 (Sig. = 0,000). The therapeutic combination Method (combined foot spa therapy and Bueger's Allen Exercises) is very effective in increasing the value of ABI in elderly DM. It is important for families and nurses to give motivation to the elderly with DM type 2 to do foot spa and Allen Bueger’s Exercise as alternative therapies to prevent foot complications. Keywords: Diabetes Mellitus; Elderly; Foot Spa; Bueger’s Allen Exercises; Ankle Brachial Index/ABI.